2012
DOI: 10.1590/s0100-879x2012007500120
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine intake by patients with autosomal dominant polycystic kidney disease

Abstract: Because caffeine may induce cyst and kidney enlargement in autosomal dominant polycystic kidney disease (ADPKD), we evaluated caffeine intake and renal volume using renal ultrasound in ADPKD patients. Caffeine intake was estimated by the average of 24-h dietary recalls obtained on 3 nonconsecutive days in 102 ADPKD patients (68 females, 34 males; 39 ± 12 years) and compared to that of 102 healthy volunteers (74 females, 28 males; 38 ± 14 years). The awareness of the need for caffeine restriction was assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…96 High caffeine intake may, therefore, be a risk factor for cyst enlargement and ADPKD progression, although a small clinical study has suggested no correlation between mild caffeine intake and TKV by ultrasound. 97 Nevertheless, it is recommended to counsel patients with ADPKD to limit their caffeine intake.…”
Section: Birth Weightmentioning
confidence: 99%
“…96 High caffeine intake may, therefore, be a risk factor for cyst enlargement and ADPKD progression, although a small clinical study has suggested no correlation between mild caffeine intake and TKV by ultrasound. 97 Nevertheless, it is recommended to counsel patients with ADPKD to limit their caffeine intake.…”
Section: Birth Weightmentioning
confidence: 99%
“…Caffeine is avoided in some cases, such as autosomal dominant polycystic kidney disease, due to prior awareness of the patients of need for restriction, because caffeine may induce cyst and kidney enlargement (45). However, in other cases, in spite of not having nutritional value, caffeine has been used as an ergogenic substance because it improves performance in long-term physical activities.…”
Section: Introductionmentioning
confidence: 99%
“…However, a majority of these patients (63%) had previously been advised to lower coffee consumption, and the mean coffee intake was significantly lower compared to healthy controls (86 ± 77 vs. 134 ± 116 mg/day, p ≤ 0.001) [39] .…”
Section: Other (Lifestyle) Factorsmentioning
confidence: 88%
“…Hypothetically, caffeine has a specific deleterious effect in PKD via PDE inhibition, but when analyzing the effects of caffeine intake in a case-control study in 102 van ADPKD patients, no associations were found between coffee intake and eGFR or TKV [39] . However, a majority of these patients (63%) had previously been advised to lower coffee consumption, and the mean coffee intake was significantly lower compared to healthy controls (86 ± 77 vs. 134 ± 116 mg/day, p ≤ 0.001) [39] .…”
Section: Other (Lifestyle) Factorsmentioning
confidence: 98%